POTENSI MADU MURNI HETEROTRIGONA ITAMA SEBAGAI SUBSTITUSI GULA KRISTAL PUTIH PADA PEMBUATAN TEH LEMON DINGIN POTENTIAL OF Heterotrigona itama PURE HONEY AS A SUBSTITUTE FOR WHITE CRYSTAL SUGAR IN COLD LEMON TEA - Riyanto, Exeldo; Sapta Zuidar, Ahmad; Herdiana, Novita; Nawansih, Otik (Jurusan Teknologi Hasil Pertanian, 2023)
Today, there are still very few product variations for product development from Heterotrigona itama pure honey, so it is necessary to develop Heterotrigona itama pure honey products. This study aims to determine the best Heterotrigona itama pure honey formulation for making cold lemon tea. The research consisted of three stages: dehumidification of Heterotrigona itama honey, formulation of cold lemon tea drink, and continued testing in the form of hedonic tests and proximate analysis of the best formula. The research used a completely randomized design (CRD) with the formulation of Heterotrigona itama honey and white crystal sugar, including 45 grams of sugar (F0), 23 grams of honey and 33.75 grams of sugar (F1), 46 grams of honey and 22.5 grams of sugar (F2), 69 grams of honey and 11.25 grams of sugar (F3), and 92 grams of honey (F4) with F0 as the control formulation. The data were analyzed using variance (ANOVA) followed by the Honest Significant Difference (BNJ) test. The formulation of Heterotrigona itama honey with a concentration of 46 grams and white crystalline sugar with a concentration of 22.5 grams (F2) in 500 ml of water is the best formula. The public accepts it for making cold lemon tea fresh drinks with a pH value of 3.09, reducing sugar of 4.6645 %, ash of 0.391 %, and total titrated acid of 2.4826%.